SIMULATION OF MAKING WALL COLOR CAT USING BORLAND DELPHI - Teddy Kusabriandi Wallad; Sahni Damerianta. Skom. MMSi (Jurnal Sistem Informasi, 2004)
On scientific writing, the writer tries to discuss the simulation technique to apply indetermining the composition and the ratio of wall paint color. Where at this writingare also discussed how to apply the basic theory of color on the computer, alongcalculations used in engineering simulation.In writing, the authors make applications with Borland Delphi version 5, with the aimto facilitate the workers in determining the composition of a color, so it can reduceerrors in processing wall paint.